Формирование и развитие творческой деятельности у детей с ограниченными возможностями здоровья - Krasnozhon I. S. (Pedagogy and psychology: development prospects, 2017)
Creation of conditions for development of creative abilities of children with disabilities, creating conditions for successful adaptation in the modern world!
Keywords: проект; творческие способности; дети с ОВЗ; creativity; children with disabilities; project